IDENTIFIKASI JENIS TANAH TERHADAP EFISIENSI WAKTU ALAT BERAT DRILLING RIG PADA PEKERJAAN PONDASI BORE PILE. - Mafrucha, Hanim; Triarso, Arik (Jurnal Vokasi Teknik Sipil, 2026)
Using a drilling rig for pile drilling can significantly improve work efficiency. To determine the time efficiency of drilling operations, it is necessary to measure and analyze the productivity of the drilling rig. Soil characteristics, the operator, and weather are factors that can influence the productivity of heavy equipment operations. Soil sondir or CPT (Cone Penetration Test) and SPT (Standard Penetration Test) demonstrate that soil characteristics vary across the drilling site, resulting in varying drilling times at each drilling location. The study aimed to interpret the productivity of the drilling rig by identifying the characteristics of the soil drilled during the drilling process using field observations. The interpretation revealed that the SR65 2022 drilling rig had a productivity of 16.18 m/hour, with a time efficiency of 50%. The characteristics of the drilled soil, based on the SPT (Standard Penetration Test) and CPT (Cone Penetration Test) results, indicate that the soil is predominantly clay or dense.